Assessing the rationale in strategic alliances: Gazprom's expansion into the Finnish natural gas market - Peeter Vahtra; Harri Lorentz (Journal for East European Management Studies, 2005)
The paper presents a hybrid model for the consideration of organisational governance forms in industrial relationships, which is then utilised in the analysis of a specific case concerning Russian Gazprom's operations in Finland as the sole supplier of natural gas to the Finnish market. Such considerations regarding foreign involvement in strategic industries from a national point of view are of vital importance, as Russian energy companies expand their operations in Europe and other parts of the world. The paper elaborates on Finnish - Russian economic relations in general and provides an outlook on the operation of Gazprom in particular. – – Der Aufsatz präsentiert ein Hybridmodell für die Einbeziehung verschiedener Formen von Organisationsführung in industriellen Beziehungen, anhand dessen die Operationen der russischen Gazprom, dem einzigen Erdgaslieferanten in Finnland, analysiert werden. Derartige Erwägungen das ausländische Engagement in strategischen Industrien betreffend, sind aus der nationalen Sicht immens wichtig, da russische Energiekonzerne ihre Operationen nicht nur in Europa ausweiten. Der Aufsatz befasst sich mit den russisch-finnischen Wirtschaftsbeziehungen im allgemeinen und bietet einen Ausblick auf die Operationen von Gazprom im speziellen.
Keywords: 650; Strategic alliances; energy; Russia; FDI; organisational governance